Linked vehicle model: A simple car-following model for automated vehicles. (February 2021) - Xiao, Yonggang; Liu, Yanbing; Song, Xiuli; Wu, Yunjun
The expectation from automated vehicles has been increasing in recent years. Potential advantages for automated vehicles include driving safety, traffic efficiency, and positive environmental outcomes. To evaluate the extent to which automated vehicles are advantageous against conventional vehicles, this paper presents a simple car-following model, named the linked vehicle model, which reflects the capabilities of automated vehicles and the interaction between adjacent automated vehicles. The idea behind linked vehicle model is inspired by the collective motion of self-propelled particles in nature and the study of vehicle platooning from the Safe Road Trains for the Environment project. Moreover, the model is integrated into a traffic simulator in order to evaluate the performance of automated vehicles in an ideal circumstance. Comparisons with other representative car-following models are also provided, and they show that linked vehicle model achieves both optimal microscopic and macroscopic performance. Simulated results also show that linked vehicle model attains the best fuel economy and the lowest pollutant emissions.